Bright tricolor ultrabroad-band emission carbon dots for white light-emitting diodes with a 96.5 high color rendering index. Issue 4 (18th December 2019) - Li, Xiaoxi; Wang, Zifei; Liu, Yang; Zhang, Weiguang; Zhu, Chaofeng; Meng, Xiangeng
Abstract : Synthesis of tricolor ultrabroad-band emissive CDs and luminescence films for WLEDs with high CRI and adjustable CCT. Abstract : Fluorescent carbon dots (CDs) have emerged as promising materials for white light-emitting diodes (WLEDs) on account of carbon's intrinsic merits of high stability, low cost, and environment-friendliness. However, CDs usually give relatively narrow emission with full width at half maximum within 70–90 nm, which fundamentally restrains construction of CDs-based WLEDs with high color rendering index (CRI). Here, we demonstrate tricolor ultrabroad-band (109–120 nm) emissive CDs (Tri-CDs) with a quantum yield (QY) up to 21–64% by a one-pot solvothermal route. Experimental investigations reveal that tunable emissions of these CDs are based on differently sized sp 2 conjugated domains and the content of graphitic nitrogen, which can be modulated by controlling the carbonization and deamination processes during solvothermal reactions. The ultrabroad-band emission spectra of Tri-CDs originate from broad distribution of the particle size. A WLED with Commission Internationale de l'Eclairage (CIE) color coordinate of (0.362, 0.370) and high CRI of 96.5 is fabricated by integrating Tri-CDs films with an ultraviolet LED chip. This work opens up a new opportunity for the development of high CRI CDs-based WLEDs.